Analysis of Illegal Interception of a Computer Data Transmission Crime in Romanian Legislation - MOISE, Adrian Cristian (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The crime of illegal interception of a computer data transmission is provided in the Article 361 of the Romanian Criminal Code. The criminalizing of this kind of act is intended to protect the confidentiality of computer data, data which is in the process of being sent, against their interception without right. The text of the Article 361 from the Romanian Criminal Code represents a transposition of Article 3 of the Council of Europe Convention on cybercrime and of Article 6 of the Directive 2013/40/EU on attacks against information systems.